A polyurethane composite and a method for producing the same
Patent Information
- Application Number
- CN202611377814.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
[0008]但是,当前纤维复合材料用聚氨酯树脂仍存在高玻纤含量下浸润不充分、界面结合弱,强度难以进一步提升
1、本发明通过纯化去除玻璃纤维表面残留有机物,同时,纤维表面硅羟基(Si-OH)密度显著提高,为后续正硅酸乙酯的化学锚定提供活性位点;在酸性条件下,正硅酸乙酯水解在纤维表面沉积一层SiO2层,使得纤维表面粗糙,与基体嵌接或啮合,产生机械性的互锁现象, 有利于在纤维与树脂之间形成较强的物理结合力;然后表面原位沉积一层聚多巴胺(PDA)涂层。PDA本身富含胺基(-NH2)、亚胺基(-NH-)和吲哚氮;这些含氮官能团在后续聚氨酯反应中可与异氰酸酯(-NCO)反应生成脲键(-NH-CO-NH-),在玻纤-树脂界面形成化学键合,另外,PDA涂层还含有丰富的邻苯二酚/醌基团,可与聚氨酯硬段形成强氢键,进一步提升界面相容性,显著提高玻纤表面能,改善树脂润湿性。
Smart Images

Figure CN122878740A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane technology, and more specifically to a polyurethane composite material and its preparation method. Background Technology
[0002] Fiber-reinforced resin matrix composites are widely used in construction, transportation, wind power, aerospace, and other fields due to their lightweight, high strength, and high designability. Their performance largely depends on the matrix resin. The current status of mainstream matrix resins is as follows: Traditional pultrusion / composite processes have long used unsaturated polyesters, vinyl esters, phenolic resins, and epoxy resins. Unsaturated polyesters and vinyl esters release volatile organic compounds (VOCs) such as styrene during curing, and the matrix is brittle with poor impact resistance and fatigue resistance. Although epoxy resins have better strength and heat resistance, they have high mixing viscosity (which is not conducive to fiber wetting under high glass fiber content), slow curing speed, and are brittle with low toughness.
[0003] Polyurethane (PU) resins offer advantages such as low viscosity, rapid curing at room to medium temperatures, no styrene volatilization, and good toughness. They can significantly increase glass fiber content, allowing pultruded composites to achieve a flexural modulus approaching that of aluminum, while reducing production costs compared to vinyl ester / epoxy systems. Covestro Baydur® PUL, Huntsman, and domestic companies have all launched two-component polyurethane systems specifically for pultrusion.
[0004] Currently, polyurethane composite materials mainly include the following technologies: Prepolymer method: A prepolymer is synthesized by reacting polyether polyol with diphenylmethane diisocyanate at around 50°C, and then cast and impregnated with glass fibers. Studies have shown that the prepolymer has the lowest initial viscosity and the longest pot life when the polymerization temperature is 50°C. With a glass fiber content of 55 wt%, the tensile strength is 794 MPa and the flexural strength is 846 MPa. However, when the glass fiber content exceeds 65 wt%, problems such as insufficient resin between fibers, interfacial debonding, and performance degradation occur.
[0005] Two-component direct mixing method: For example, CN107793548A uses low-viscosity isocyanate and high-functionality polymer polyol with small molecule chain extender, with an initial viscosity of 200-500 mPa·s and a reinforcing material content of more than 80%; CN113861376A discloses a polyurethane composition with a mixing viscosity of about 200 mPa·s and a gel time of more than 10 hours, which can be used to prepare composite materials with a glass fiber content of 80 wt% by pultrusion in an open impregnation tank.
[0006] Hydrolysis resistance modification: CN110172134B addresses the problem of easy hydrolysis of polyester-type polyurethane, but points out that the addition of polycarbonate diol will increase the overall viscosity of the resin and is not conducive to the resin's wetting of fibers.
[0007] Latent catalytic technology: WO2015 / 078740 proposes a polyurethane system with a long pot life and rapid curing. Microencapsulated catalysts and blocked catalysts are also known methods for balancing pot life and curing speed.
[0008] However, current polyurethane resins used in fiber composites still suffer from insufficient wetting and weak interfacial bonding at high glass fiber content, making it difficult to further improve strength. Increasing the glass fiber content is a direct way to reduce costs, but existing systems lack the ability to penetrate dense fiber bundles and the design for interfacial chemical bonding. Summary of the Invention
[0009] The purpose of this invention is to propose a polyurethane composite material and its preparation method. Through surface chemical modification, the three reinforcing agents, glass fiber, montmorillonite, and calcium carbonate, are all made to carry reactive functional groups and are chemically bonded to the matrix network during the in-situ polymerization of polyurethane. At the same time, Si-O-Si hybrid crosslinking is introduced, ultimately achieving a balance between high glass fiber content, high strength, high modulus, long life and low cost.
[0010] The technical solution of this invention is implemented as follows: This invention provides a method for preparing a polyurethane composite material, comprising the following steps: S1. After purifying the glass fiber, a SiO2 layer is deposited on the surface to roughen it, and then the surface nitrogen content is increased by chemical grafting to obtain modified glass fiber; S2. Organic amine-intercalated montmorillonite is reacted with isocyanate to obtain modified intercalated montmorillonite; S3. Modified nano-calcium carbonate is obtained by modifying nano-calcium carbonate with a silane coupling agent; S4. Add the modified intercalated montmorillonite and modified nano-calcium carbonate to an organic solvent, and disperse them evenly by ultrasonication to obtain a modified solution; S5. Dehydrate polytetrahydrofuran glycol, add modified liquid and modified glass fiber at 40-60℃, stir and mix evenly, add diphenylmethane diisocyanate and catalyst, heat to 70-90℃, react at a constant temperature for 1-3 hours to obtain prepolymer, cool to 40-50℃, add chain extender, react for 0.5-1 hours, degas under vacuum, dry, and cure to obtain polyurethane composite material; the chain extender includes silane coupling agent and 1,4-butanediol, with a mass ratio of 5-10:8-15.
[0011] As a further improvement of the present invention, the method for preparing the modified glass fiber in step S1 is as follows: S101. Wash and dry the glass fiber, add potassium dichromate and concentrated sulfuric acid, stir to react, filter, wash, add hydrogen peroxide to react, and obtain purified glass fiber; S102. Add purified glass fiber to ethanol, add hydrochloric acid, heat and stir to react, add surface reaction liquid dropwise, raise the temperature to 80-90℃ and stir to react, and obtain surface roughened glass fiber. S103. Add surface-roughened glass fibers to Tris-HCl solution, add dopamine hydrochloride and emulsifier, stir and react to obtain modified glass fibers.
[0012] As a further improvement of the present invention, in step S101, the stirring reaction time is 10-30 min; in step S102, the surface reaction solution is an emulsion containing tetraethyl orthosilicate, water, ethanol, Tween 80 and hexadecyltrimethylammonium bromide, with a mass ratio of 8-10:15-20:80-120:2-5:1-3, the heating and stirring reaction temperature is 45-55℃, the time is 20-40 min, and the stirring reaction time is 2-4 h when the temperature is raised to 80-90℃; in step S103, the pH value of the Tris-HCl solution is 8.5-9.5, the mass ratio of the surface roughening glass fiber, dopamine hydrochloride and emulsifier is 10:2-3:0.2-0.5, and the emulsifier is at least one of Tween 20, Tween 40, Tween 60, Tween 80 and Tween 85.
[0013] As a further improvement of the present invention, in step S2, the method for preparing the modified intercalated montmorillonite is as follows: S201. Sodium-based montmorillonite is added to water, and an acidic organic amine solution is added dropwise. The mixture is stirred to prepare organic amine-intercalated montmorillonite. S202. Add dried organic amine intercalated montmorillonite to an anhydrous organic solvent, add diphenylmethane diisocyanate, heat and stir to react, and obtain modified intercalated montmorillonite.
[0014] As a further improvement of the present invention, in step S201, the mass ratio of sodium-based montmorillonite to organic amine is 5-8:1-1.6, the organic amine is selected from at least one of dodecylamine, tetradecylamine, hexadecylamine, and octadecylamine, the acidic organic amine solution is prepared by dissolving the organic amine in water and adjusting the pH of the solution to 6-7, and the stirring time is 0.5-1.5 h; in step S202, the mass ratio of organic amine intercalated montmorillonite to diphenylmethane diisocyanate is 6-10:1-1.6, the heating and stirring reaction temperature is 75-85℃, and the time is 0.5-1 h.
[0015] As a further improvement of the present invention, in step S3, the preparation method of modified nano-calcium carbonate is as follows: silane coupling agent KH550, water and ethanol are mixed in a volume ratio of 1:0.5-1.5:10-15, heated to 45-55℃ for hydrolysis for 0.5-1.5h to obtain hydrolysate, which is then mixed evenly with nano-calcium carbonate alcohol-water dispersion and heated under reflux for 4-6h to obtain modified nano-calcium carbonate; The volume ratio of the hydrolysate to the nano-calcium carbonate alcohol aqueous dispersion is 1:10-15. The nano-calcium carbonate alcohol-water dispersion contains 10-20% calcium carbonate by mass, and the solvent is a mixture of ethanol and water in a volume ratio of 8-10:1.
[0016] As a further improvement of the present invention, in step S4, the mass ratio of the modified intercalated montmorillonite, the modified nano-calcium carbonate and the organic solvent is 5-10:3-8:100.
[0017] As a further improvement of the present invention, in step S5, the mass ratio of polytetrahydrofuran diol, modified liquid, diphenylmethane diisocyanate, modified glass fiber, and chain extender is 100:90-110:40-55:340-360:11-20, the silane coupling agent is KH602 or KH792, the aging temperature is 90-110℃, the time is 10-15h, and the catalyst is dibutyltin dilaurate.
[0018] The present invention further protects a polyurethane composite material prepared by the above-described preparation method.
[0019] The present invention has the following beneficial effects: 1. This invention removes residual organic matter from the surface of glass fibers through purification. Simultaneously, the density of silanol groups (Si-OH) on the fiber surface is significantly increased, providing active sites for the subsequent chemical anchoring of tetraethyl orthosilicate. Under acidic conditions, tetraethyl orthosilicate hydrolyzes, depositing a SiO2 layer on the fiber surface, roughening the fiber surface and enabling it to interlock or mesh with the matrix, generating a mechanical interlocking phenomenon that facilitates a strong physical bond between the fiber and resin. Then, a polydopamine (PDA) coating is deposited in situ on the surface. PDA itself is rich in amine (-NH2), imine (-NH-), and indole nitrogen groups. These nitrogen-containing functional groups can react with isocyanate (-NCO) in the subsequent polyurethane reaction to form urea bonds (-NH-CO-NH-), forming chemical bonds at the glass fiber-resin interface. Furthermore, the PDA coating contains abundant catechol / quinone groups, which can form strong hydrogen bonds with the hard segments of the polyurethane, further improving interfacial compatibility, significantly increasing the surface energy of the glass fiber, and improving resin wettability.
[0020] 2. In this invention, organic amines (such as dodecylamine and octadecylamine) are protonated under acidic conditions to form ammonium ions, which then enter the interlayer of montmorillonite through a cation exchange reaction. The long-chain alkyl groups of the organic amines significantly increase the interlayer spacing of montmorillonite, creating conditions for the subsequent insertion and exfoliation of polyurethane molecular chains. After returning to neutral, the interlayer organic amines can react with diphenylmethane diisocyanate (MDI), resulting in the grafting of MDI segments with isocyanate end groups or urea bonds onto the montmorillonite. In the subsequent S5 prepolymerization reaction, these grafted MDI segments can directly react with polytetrahydrofuran glycol (PTMG), allowing montmorillonite to be covalently embedded into the polyurethane hard segment network, achieving in-situ polymerization of polyurethane chains in the interlayer. The polymerization driving force is used to exfoliate and disperse the montmorillonite layers, greatly improving the compatibility of montmorillonite in the resin. This invention has found that, compared with the commonly used intercalating agent hexadecyltrimethylammonium bromide, organic amines have a better modification effect.
[0021] 3. In this invention, the surface of the modified nano-calcium carbonate is controlled by the hydrolysis of KH550 (γ-aminopropyltriethoxysilane) in a weakly acidic water-ethanol system. The generated silanol (Si-OH) undergoes dehydration condensation with the hydroxyl groups or oxides on the surface of nano-CaCO3 to form Si-O-Ca covalent bonds, firmly grafting KH550 onto the CaCO3 surface. The amino group (-NH2) at the other end of KH550 is exposed and can react with the -NCO of MDI in the S5 polyurethane reaction to form urea bonds, transforming the nano-CaCO3 from a "physical filler" to a "chemical crosslinking point," becoming part of the polyurethane network. At the same time, it can also react with the isocyanates on the modified intercalated montmorillonite to form a network modified structure, further improving the crosslinking effect. The nano-CaCO3 has a toughening and reinforcing effect, not only improving the bending strength and bending modulus of elasticity, heat distortion temperature and dimensional stability of the material, but also giving the material heat resistance.
[0022] 4. The chain extender of this invention contains a silane coupling agent with two amino groups and 1,4-butanediol (BDO). BDO, as a small-molecule diol chain extender, reacts with the terminal NCO prepolymer to extend hard segment chains, increase hard segment content, and improve material strength and modulus. The silane coupling agent contains dual active functional groups; its organic functional group (-NH2) reacts with the terminal NCO to introduce siloxane groups into the polyurethane backbone. Simultaneously, its hydrolyzable alkoxysilane undergoes hydrolysis and condensation during trace amounts of moisture or post-curing in the system, forming a Si-O-Si inorganic crosslinking network. Therefore, the polyurethane system forms an organic-inorganic hybrid network: the organic polyurethane segments provide toughness and elasticity, while the inorganic Si-O-Si network provides rigidity and heat resistance. The Si-O-Si crosslinking network introduced by KH602 / KH792 has high thermal stability, which improves the thermal decomposition temperature of the material. At the same time, this inorganic network has excellent barrier properties against water molecules. Combined with the hydrolysis-resistant ether bond structure of PTMG itself, the composite material has the characteristics of long life and resistance to damp heat aging.
[0023] 5. This invention pre-forms a stable modified liquid by adding modified intercalated montmorillonite and modified nano-calcium carbonate to an organic solvent. This modified liquid is then mixed with modified glass fibers and added to a low-viscosity PTMG / MDI system. This effectively reduces the resin-fiber interfacial tension, ensuring sufficient wetting even with high glass fiber content. Furthermore, because all three modified materials undergo surface treatment, no agglomeration or aggregation occurs after mixing, thus overcoming the bottleneck of insufficient wetting and interfacial debonding in existing technologies with high glass fiber content.
[0024] 6. In this invention, modified glass fiber serves as the main load-bearing phase, achieving efficient stress transfer through strong interfacial bonding. The exfoliated and dispersed montmorillonite layers provide a "nano-reinforcement" effect, improving modulus and barrier properties. Nano-CaCO3 is dispersed in the matrix through KH550 bridging, bearing part of the load and preventing crack propagation. The three types of reinforcement are integrated with the matrix through chemical bonds, enabling the composite material to maintain toughness while significantly improving tensile strength, flexural strength, and modulus.
[0025] 7. By increasing the glass fiber content and using conventional industrial raw materials, this invention meets the requirements for high performance while having a lower overall cost than the vinyl ester / epoxy system, which is in line with the development trend of low cost of new composite materials. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a SEM image of the modified glass fiber prepared in Example 1.
[0028] Figure 2 The image shows a SEM image of the polyurethane composite material prepared in Example 1. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Preparation method of potassium dichromate and concentrated sulfuric acid cleaning solution: Dissolve 25g of potassium dichromate powder in 50g of water at 60℃, then add 450mL of industrial sulfuric acid (98%) in small amounts several times while stirring, and mix evenly to obtain the solution.
[0031] Nano-calcium carbonate, with an average particle size of <100nm.
[0032] Example 1 This embodiment provides a method for preparing a polyurethane composite material, including the following steps: S1. After purifying the glass fiber, a SiO2 layer is deposited on the surface to roughen it, and then the surface nitrogen content is increased by chemical grafting to obtain modified glass fiber; include: S101. Wash and dry the chopped glass fibers, soak them in a washing solution of potassium dichromate and concentrated sulfuric acid, stir for 10 min, filter, wash, add hydrogen peroxide to react with the residual potassium dichromate until complete, filter, wash, dry, and obtain purified glass fibers. S102. Add 10g of purified glass fiber to 100mL of ethanol, add hydrochloric acid to adjust the pH to 5-6, heat to 45℃, stir for 40min, add surface reaction solution dropwise, raise the temperature to 80℃, stir for 4h, filter, wash, dry, and obtain surface roughened glass fiber. Preparation of surface reaction solution: 8g tetraethyl orthosilicate, 15g water, 80g ethanol, 2g Tween 80 and 1g hexadecyltrimethylammonium bromide were mixed evenly to form an emulsion.
[0033] S103. Add 10g of surface-roughened glass fiber to 100mL of Tris-HCl solution with pH value of 8.5-9.5, add 2g of dopamine hydrochloride and 0.2g of Tween 80, stir and react at 50℃ for 3h, filter, wash, dry, and obtain modified glass fiber. Figure 1 The image shows a SEM image of the modified glass fiber.
[0034] S2. Organic amine-intercalated montmorillonite is reacted with isocyanate to obtain modified intercalated montmorillonite; Includes the following steps: S201. Add 5g of sodium montmorillonite to 400mL of water, add 100mL of acidic organic amine solution dropwise, stir at 800r / min for 1h, filter, wash, and dry to obtain organic amine intercalated montmorillonite; The acidic organic amine solution is prepared by dissolving 1g of tetradecylamine in 100mL of water, adjusting the pH of the solution to 6-7 with hydrochloric acid, and stirring for 0.5h. S202. Add 6g of dried organic amine intercalated montmorillonite to 150mL of anhydrous N,N-dimethylformamide, add 1g of diphenylmethane diisocyanate, heat to 75℃, stir and react for 1h, filter, wash with anhydrous acetone, and dry to obtain modified intercalated montmorillonite. S3. Mix silane coupling agent KH550, water and ethanol at a volume ratio of 1:0.5:10, heat to 45℃ for 1.5h to hydrolyze and obtain hydrolysate. Mix 10mL of hydrolysate with 100mL of 20% nano calcium carbonate alcohol aqueous dispersion (the solvent is a mixture of ethanol and water at a volume ratio of 8:1) evenly, heat under reflux for 4h, filter, wash and dry to obtain modified nano calcium carbonate. S4. Add 5g of modified intercalated montmorillonite and 3g of modified nano-calcium carbonate to 100mL of N,N-dimethylformamide, and sonicate for 2h to obtain the modified solution; S5. Dehydrate 100g of polytetrahydrofuran diol 2000, add 90g of modified liquid and 340g of modified glass fiber at 40℃, stir and mix for 30min, add 40g of diphenylmethane diisocyanate and 1 drop of catalyst dibutyltin dilaurate, heat to 70℃, react at a constant temperature for 3h, remove solvent by vacuum distillation to obtain prepolymer, cool to 40℃, add 11g of chain extender (including silane coupling agent KH602 and 1,4-butanediol, mass ratio 5:8), react for 1h, degas under vacuum, dry, and cure at 90℃ for 15h to obtain polyurethane composite material. Figure 2 The image shows a SEM image of the prepared polyurethane composite material.
[0035] Example 2 This embodiment provides a method for preparing a polyurethane composite material, including the following steps: S1. After purifying the glass fiber, a SiO2 layer is deposited on the surface to roughen it, and then the surface nitrogen content is increased by chemical grafting to obtain modified glass fiber; include: S101. Wash and dry the chopped glass fibers, soak them in a washing solution of potassium dichromate and concentrated sulfuric acid, stir for 30 min, filter, wash, add hydrogen peroxide to react with the residual potassium dichromate until complete, filter, wash, dry, and obtain purified glass fibers. S102. Add 10g of purified glass fiber to 100mL of ethanol, add hydrochloric acid to adjust the pH to 5-6, heat to 55℃, stir for 20min, add surface reaction solution dropwise, raise the temperature to 90℃, stir for 2h, filter, wash, dry, and obtain surface roughened glass fiber. Preparation of surface reaction solution: 10g tetraethyl orthosilicate, 20g water, 120g ethanol, 5g Tween 80 and 3g hexadecyltrimethylammonium bromide were mixed evenly to form an emulsion.
[0036] S103. Add 10g of surface-roughened glass fiber to 100mL of Tris-HCl solution with pH value of 8.5-9.5, add 3g of dopamine hydrochloride and 0.5g of Tween 80, stir and react at 50℃ for 3h, filter, wash, dry, and obtain modified glass fiber. S2. Organic amine-intercalated montmorillonite is reacted with isocyanate to obtain modified intercalated montmorillonite; Includes the following steps: S201. Add 8g of sodium montmorillonite to 400mL of water, add 100mL of acidic organic amine solution dropwise, stir at 800r / min for 1h, filter, wash, and dry to obtain organic amine intercalated montmorillonite; The acidic organic amine solution was prepared by dissolving 1.6 g of hexadecylamine in 100 mL of water, adjusting the pH of the solution to 6-7 with hydrochloric acid, and stirring for 1.5 h. S202. Add 6-10g of dried organic amine intercalated montmorillonite to 150mL of anhydrous N,N-dimethylformamide, add 1.6g of diphenylmethane diisocyanate, heat to 85℃, stir and react for 0.5h, filter, wash with anhydrous acetone, and dry to obtain modified intercalated montmorillonite. S3. Mix silane coupling agent KH550, water and ethanol in a volume ratio of 1:1.5:15, heat to 55℃ and hydrolyze for 0.5h to obtain hydrolysate. Mix 10mL of hydrolysate with 150mL of 10% nano calcium carbonate alcohol aqueous dispersion (the solvent is a mixture of ethanol and water in a volume ratio of 10:1) evenly, heat under reflux for 6h, filter, wash and dry to obtain modified nano calcium carbonate. S4. Add 10g of modified intercalated montmorillonite and 8g of modified nano-calcium carbonate to 100mL of N,N-dimethylformamide, and sonicate for 2h to obtain the modified solution; S5. Dehydrate 100g of polytetrahydrofuran glycol 2000, add 110g of modified liquid and 360g of modified glass fiber at 60℃, stir and mix for 30min, add 55g of diphenylmethane diisocyanate and 1 drop of catalyst dibutyltin dilaurate, heat to 90℃, react at a constant temperature for 1h, remove solvent by vacuum distillation to obtain prepolymer, cool to 50℃, add 20g of chain extender (including silane coupling agent KH602 and 1,4-butanediol, mass ratio 10:15), react for 0.5h, degas under vacuum, dry, and cure at 110℃ for 10h to obtain polyurethane composite material.
[0037] Example 3 This embodiment provides a method for preparing a polyurethane composite material, including the following steps: S1. After purifying the glass fiber, a SiO2 layer is deposited on the surface to roughen it, and then the surface nitrogen content is increased by chemical grafting to obtain modified glass fiber; include: S101. Wash and dry the chopped glass fibers, soak them in a washing solution of potassium dichromate and concentrated sulfuric acid, stir for 20 min, filter, wash, add hydrogen peroxide to react with the residual potassium dichromate until complete, filter, wash, dry, and obtain purified glass fibers. S102. Add 10g of purified glass fiber to 100mL of ethanol, add hydrochloric acid to adjust the pH to 5-6, heat to 50℃, stir for 30min, add surface reaction solution dropwise, raise the temperature to 85℃, stir for 3h, filter, wash, dry, and obtain surface roughened glass fiber. Preparation of surface reaction solution: 9g tetraethyl orthosilicate, 17g water, 100g ethanol, 3g Tween 80 and 2g hexadecyltrimethylammonium bromide were mixed evenly to form an emulsion.
[0038] S103. Add 10g of surface-roughened glass fiber to 100mL of Tris-HCl solution with pH value of 8.5-9.5, add 2.5g of dopamine hydrochloride and 0.35g of Tween 80, stir and react at 50℃ for 3h, filter, wash, dry, and obtain modified glass fiber. S2. Organic amine-intercalated montmorillonite is reacted with isocyanate to obtain modified intercalated montmorillonite; Includes the following steps: S201. Add 6.5g of sodium montmorillonite to 400mL of water, add 100mL of acidic organic amine solution dropwise, stir at 800r / min for 1h, filter, wash, and dry to obtain organic amine intercalated montmorillonite; The acidic organic amine solution was prepared by dissolving 1.3g of octadecylamine in 100mL of water, adjusting the pH of the solution to 6-7 with hydrochloric acid, and stirring for 1 hour. S202. Add 8g of dried organic amine intercalated montmorillonite to 150mL of anhydrous N,N-dimethylformamide, add 1.3g of diphenylmethane diisocyanate, heat to 80℃, stir and react for 1h, filter, wash with anhydrous acetone, and dry to obtain modified intercalated montmorillonite. S3. Mix silane coupling agent KH550, water and ethanol in a volume ratio of 1:1:12, heat to 50℃ and hydrolyze for 1 h to obtain hydrolysate. Mix 10 mL of hydrolysate with 120 mL of 15% nano-calcium carbonate alcohol aqueous dispersion (the solvent is a mixture of ethanol and water in a volume ratio of 9:1), heat under reflux for 5 h, filter, wash and dry to obtain modified nano-calcium carbonate. S4. Add 7g of modified intercalated montmorillonite and 5g of modified nano-calcium carbonate to 100mL of N,N-dimethylformamide, and sonicate for 2h to obtain the modified solution; S5. Dehydrate 100g of polytetrahydrofuran glycol 2000, add 100g of modified liquid and 350g of modified glass fiber at 50℃, stir and mix for 30min, add 47g of diphenylmethane diisocyanate and 1 drop of catalyst dibutyltin dilaurate, heat to 80℃, react at a constant temperature for 2h, remove solvent by vacuum distillation to obtain prepolymer, cool to 45℃, add 16g of chain extender (including silane coupling agent KH792 and 1,4-butanediol, mass ratio 7:11), react for 1h, degas under vacuum, dry, and cure at 100℃ for 12h to obtain polyurethane composite material.
[0039] Comparative Example 1: Compared with Example 3, the only difference is that step S102 is not performed in step S1, and step S103 is performed directly after step S101 is completed.
[0040] Comparative Example 2: Compared with Example 3, the only difference is that step S103 was not performed in step S1, and the product obtained in step S102 was subjected to subsequent reactions.
[0041] Comparative Example 3: Compared with Example 3, the only difference is that steps S102 and S103 were not performed in step S1, and the product obtained in step S101 was subjected to subsequent reactions.
[0042] Comparative Example 4: Compared with Example 3, the only difference is that in step S201, octadecylamine is replaced with an equal amount of hexadecyltrimethylammonium bromide.
[0043] Comparative Example 5: Compared with Example 3, the only difference is that step S202 was not performed in step S2, and the product obtained in step S201 was directly carried out in subsequent reactions.
[0044] Comparative Example 6: Compared with Example 3, the only difference is that step S3 was not performed, and the modified nano-calcium carbonate in step S4 was replaced by an equal mass of nano-calcium carbonate.
[0045] Comparative Example 7: The only difference from Example 3 is that the chain extender is only 1,4-butanediol.
[0046] Test Example 1 The polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to performance tests, and the results are shown in Table 1.
[0047] Mechanical properties: An INSTRON 3365 universal testing machine was used. The tensile specimens were dumbbell-shaped. The tensile strength and elongation at break of the nanocomposite materials were tested according to GB / T 528-2009.
[0048] Hardness: The hardness of the material was tested using a Shore D hardness tester according to the ASTM D-2240 test method.
[0049] Heat deformation temperature test: The heat deformation temperature is tested according to ASTM D-648 method.
[0050] Hydrolysis resistance test: The sample prepared according to the above standard was placed in a damp heat aging chamber at 85℃ and 85% humidity for 1000h, and then the mechanical properties were tested to determine the rate of decrease.
[0051] Table 1 ; In Comparative Example 1, the SiO2 layer deposited by the hydrolysis of tetraethyl orthosilicate roughens the fiber surface and forms a mechanical interlock. Without this layer, the physical interlocking between the fiber and the resin relies solely on the interfacial interaction of chemical grafting, which significantly weakens the physical interlocking. Under tensile load, interfacial debonding occurs prematurely, leading to a comprehensive decrease in strength, hardness, and heat distortion temperature. The bonding area of the PDA coating directly adhering to the smooth glass fiber surface is reduced, resulting in decreased coating adhesion. The coating is more prone to failure under long-term humid and hot environments, thus reducing its hydrolysis resistance.
[0052] In Comparative Example 2, the PDA coating is rich in amine (-NH2) and imine (-NH-) groups, which can react with isocyanate (-NCO) to form urea bonds (-NH-CO-NH-), forming covalent bonds. Catechol / quinone groups can form strong hydrogen bonds with the polyurethane hard segments. Without PDA, these chemical bonds and secondary bonds disappear. SiO2 roughening only provides physical interlocking but lacks chemical bridging, significantly reducing the wettability and bonding strength at the resin-fiber interface. This is manifested in a simultaneous decrease in tensile strength and elongation at break. The PDA coating itself has a barrier effect, and the urea bond network formed by its nitrogen-containing groups resists water molecules. Without PDA, the interface becomes a weak point for water penetration, and the strength reduction rate after hydrolysis increases from 12.5% to 19.5%.
[0053] In Comparative Example 3, although the density of silanol groups (Si-OH) on the surface of the purified glass fiber was increased, there was neither mechanical intercalation of the SiO2 layer nor chemical bonding and hydrogen bonding of PDA. The interface became the weakest link in the whole. The tensile strength, elongation at break, hardness and heat distortion temperature were the lowest among all groups. The unmodified glass fiber and the PU matrix did not match in modulus. After the interface debonded, the stress could not be effectively transferred, and the material fractured prematurely, which was manifested as a sharp drop in elongation.
[0054] In Comparative Example 4, the difference in intercalating agents led to different exfoliation effects. Hexadecyltrimethylammonium bromide (CTAB), a quaternary ammonium salt, enters the interlayer of montmorillonite through ion exchange. However, long-chain alkylamines (such as octadecylamine) are intercalated after protonation, exhibiting superior chain flexibility and reactivity with subsequent MDI. After organic amine intercalation, isocyanate groups are grafted onto the surface of the montmorillonite sheets. During the in-situ polymerization of polyurethane, the shear force generated by the polymerization reaction promotes the exfoliation and dispersion of the sheets. CTAB-modified montmorillonite lacks this reactivity, making it difficult to fully exfoliate the sheets. The nano-reinforcing effect is significantly weakened, and the insufficiently exfoliated montmorillonite has a reduced barrier effect against water molecules and heat, resulting in a simultaneous decrease in heat distortion temperature and hydrolysis resistance.
[0055] In Comparative Example 5, step S202 grafts MDI onto organic amine-intercalated montmorillonite, giving it -NCO groups that can react with polyether polyols / chain extenders to become part of the polyurethane network. Without this step, the montmorillonite is merely a physical filler, lacking the "anchoring" effect of chemical grafting. During polymerization, the montmorillonite layers are difficult to effectively peel and fix, easily leading to aggregation and failing to exert the "nano-reinforcement" and barrier effects. The layered structure of montmorillonite physically restricts molecular chain movement; this effect is weakened in unpeeled montmorillonite, hence the heat distortion temperature decreases by 153℃.
[0056] In Comparative Example 6, the unmodified nano-CaCO3 surface is hydrophilic (containing a large number of -OH groups), exhibiting extremely poor compatibility with the hydrophobic polyurethane matrix. It easily aggregates in organic solvents and prepolymers, failing to disperse uniformly. KH550 modification introduces active groups such as amino groups onto the CaCO3 surface, allowing it to react with -NCO, transforming the filler into network nodes that bear loads and prevent crack propagation. The unmodified CaCO3 interface with the matrix is weak, easily debonding under load and becoming a defect source. After KH550 modification, the inorganic particles of nano-CaCO3 exhibit improved interfacial bonding with the organic matrix, enhancing rigidity; unmodified particles not only fail to enhance rigidity but also reduce overall thermal stability due to aggregation.
[0057] In Comparative Example 7, BDO, as a small-molecule diol chain extender, can still extend the hard segment chain and increase the hard segment content. Therefore, its negative impact on tensile strength, hardness, and elongation is relatively small. KH602 / KH792 contains hydrolyzable alkoxysilanes, which hydrolyze and condense to form a Si-O-Si network during the curing process. Without this network, the material loses its organic-inorganic hybrid structure. The Si-O-Si bond energy is high, and the thermal stability is good. After its absence, the heat distortion temperature drops to 156℃. The Si-O-Si network has an excellent barrier effect against water molecules. Combined with the hydrolysis-resistant ether bond structure of PTMG, a long lifespan can be achieved. Without the silane coupling agent, water can easily penetrate into the interface and the matrix, leading to accelerated hydrolytic degradation.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a polyurethane composite material, characterized in that, Includes the following steps: S1. After purifying the glass fiber, a SiO2 layer is deposited on the surface to roughen it, and then the surface nitrogen content is increased by chemical grafting to obtain modified glass fiber; S2. Organic amine-intercalated montmorillonite is reacted with isocyanate to obtain modified intercalated montmorillonite; S3. Modified nano-calcium carbonate is obtained by modifying nano-calcium carbonate with a silane coupling agent; S4. Add the modified intercalated montmorillonite and modified nano-calcium carbonate to an organic solvent, and disperse them evenly by ultrasonication to obtain a modified solution; S5. Dehydrate polytetrahydrofuran glycol, add modified liquid and modified glass fiber at 40-60℃, stir and mix evenly, add diphenylmethane diisocyanate and catalyst, heat to 70-90℃, react at a constant temperature for 1-3 hours to obtain prepolymer, cool to 40-50℃, add chain extender, react for 0.5-1 hours, degas under vacuum, dry, and cure to obtain polyurethane composite material; the chain extender includes silane coupling agent and 1,4-butanediol, with a mass ratio of 5-10:8-15.
2. The preparation method according to claim 1, characterized in that, In step S1, the modified glass fiber is prepared as follows: S101. Wash and dry the glass fiber, add potassium dichromate and concentrated sulfuric acid, stir to react, filter, wash, add hydrogen peroxide to react, and obtain purified glass fiber; S102. Add purified glass fiber to ethanol, add hydrochloric acid, heat and stir to react, add surface reaction liquid dropwise, raise the temperature to 80-90℃ and stir to react, and obtain surface roughened glass fiber. S103. Add surface-roughened glass fibers to Tris-HCl solution, add dopamine hydrochloride and emulsifier, stir and react to obtain modified glass fibers.
3. The preparation method according to claim 2, characterized in that, In step S101, the stirring reaction time is 10-30 min; in step S102, the surface reaction solution is an emulsion containing tetraethyl orthosilicate, water, ethanol, Tween 80, and hexadecyltrimethylammonium bromide, with a mass ratio of 8-10:15-20:80-120:2-5:1-3, the heating and stirring reaction temperature is 45-55℃, the time is 20-40 min, and the stirring reaction time is 2-4 h when the temperature is raised to 80-90℃; in step S103, the pH value of the Tris-HCl solution is 8.5-9.5, the mass ratio of the surface roughening glass fiber, dopamine hydrochloride, and emulsifier is 10:2-3:0.2-0.5, and the emulsifier is at least one of Tween 20, Tween 40, Tween 60, Tween 80, and Tween 85.
4. The preparation method according to claim 1, characterized in that, In step S2, the modified intercalated montmorillonite is prepared as follows: S201. Sodium-based montmorillonite is added to water, and an acidic organic amine solution is added dropwise. The mixture is stirred to prepare organic amine-intercalated montmorillonite. S202. Add dried organic amine intercalated montmorillonite to an anhydrous organic solvent, add diphenylmethane diisocyanate, heat and stir to react, and obtain modified intercalated montmorillonite.
5. The preparation method according to claim 4, characterized in that, In step S201, the mass ratio of sodium-based montmorillonite to organic amine is 5-8:1-1.6, and the organic amine is selected from at least one of dodecylamine, tetradecylamine, hexadecylamine, and octadecylamine. The acidic organic amine solution is prepared by dissolving the organic amine in water and adjusting the pH of the solution to 6-7. The stirring time is 0.5-1.5 h. In step S202, the mass ratio of organic amine intercalated montmorillonite to diphenylmethane diisocyanate is 6-10:1-1.6, and the heating and stirring reaction temperature is 75-85℃ for 0.5-1 h.
6. The preparation method according to claim 1, characterized in that, In step S3, the modified nano-calcium carbonate is prepared as follows: silane coupling agent KH550, water and ethanol are mixed in a volume ratio of 1:0.5-1.5:10-15, heated to 45-55℃ for hydrolysis for 0.5-1.5h to obtain hydrolysate, which is then mixed evenly with nano-calcium carbonate alcohol-water dispersion and heated under reflux for 4-6h to obtain modified nano-calcium carbonate; The volume ratio of the hydrolysate to the nano-calcium carbonate alcohol aqueous dispersion is 1:10-15. The nano-calcium carbonate alcohol-water dispersion contains 10-20% calcium carbonate by mass, and the solvent is a mixture of ethanol and water in a volume ratio of 8-10:
1.
7. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of the modified intercalated montmorillonite, the modified nano-calcium carbonate, and the organic solvent is 5-10:3-8:
100.
8. The preparation method according to claim 1, characterized in that, In step S5, the mass ratio of polytetrahydrofuran diol, modifying liquid, diphenylmethane diisocyanate, modified glass fiber, and chain extender is 100:90-110:40-55:340-360:11-20, the silane coupling agent is KH602 or KH792, the aging temperature is 90-110℃, the time is 10-15h, and the catalyst is dibutyltin dilaurate.
9. A polyurethane composite material prepared by the preparation method according to any one of claims 1-8.
Citation Information
Patent Citations
Double-component polyurethane resin and preparation method thereof, and process for preparing polyurethane pultrusion composite material from double-component polyurethane resin
CN107793548A
A hydrolysis-resistant polyurethane pultrusion resin composite material and its preparation method
CN110172134B
Polyurethane composition for preparing composite material
CN113861376A
Polyurethane system with long pot life and rapid hardening
WO2015078740A1